STRATEGIC PLANNING FORMULATION FOR THE DEVELOPMENT OF A GREEN HOUSING ESTATE DESIGN - Jordan, Nadia Almira; Putra, Rulliannor Syah; Aprilianti, Della; Hidayat, Aisyah Delia (Journal of Architecture&ENVIRONMENT, 2024)
The rapid development of Balikpapan built environment is influenced by the development of the relocation of Indonesia’s capital city to the East Kalimantan Province. One impact that should be anticipated is the increase in immigrant and land conversion due to infrastructure expansion and the effect on the natural urban ecosystem. The disruption of the natural environment can indirectly affect welfare, such as the lack of accessibility of residents to appropriate resources. The quality of the housing environment has a fundamental significance on the quality of life; however, a measurable design approach is still unseen in the Grand City housing in Balikpapan. This research aims to formulate an improvement design strategy for a green neighborhood following the greenship criteria. Using SWOT analysis, internal and external factors were compiled in the qualitative matrix to generate design strategies. The result shows that internal and external source factors support the improvement by depicting the developed area's strengths and weaknesses. The essential enhancements for the area are the movement and connectivity and the building and energy criteria. At the same time, the other improvements are related to the provision and the development of the existing elements could improve the green innovation of the area to be more environmental-friendly.